DEVELOPMENT OF SOCIO-ECONOMIC COMPETENCE IN FUTURE SPECIALISTS OF EDUCATION BY MEANS OF DESIGNING PEDAGOGICAL BUSINESS PROJECTS - Chekina, Alena (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
The paper reveals the role of designing pedagogical business projects for the development of socio-economic competence in future specialists of education. The methodological basis of the research is constituted by competence-based and project approaches in higher education.The paper contains the author's determination of the concept "socio-economic competence of future specialists of education", the description of specifics of creation by students of business projects in the sphere of educational services. The problem of the research is formulated by means of a question: by what method the socio-economic competence of future specialists of education to be increased.The extent of development of socio-economic competence was measured by means of a system of commonly accepted techniques for the high-quality analysis of oral and written answers, conversations, observations, an expert evaluation, testing, a case measuring instruments, statistical methods analysis, in particular, calculation of percentage ratios and arithmetic averages of numbers. These tools allow us to reveal levels of readiness of all substantial components of this competence: motivational, cognitive, activity, reflexive, axiological.